Membangun Kepercayaan Publik melalui Pelayanan Publik yang Berkualitas - Sahuri, Chalid (Jurnal Ilmu Administrasi Negara, 2013)
The many sigh at bureaucracy of service of public in Indonesia show existence of indica-tion that service of public still be looked into very ugly, condition of said that if less pay attention towill cause decline theness competitiveness for public organization. Public organization which don’thave competitiveness mean the organization of indigent apply change demand or challenge epoch.in reality still be met by public organization which indigent fulfill progressively public demandcritical and multifarious, result trust of society to public organization progressively decline wherepublic no longer feel proud to the public existence of organization about his. for the purpose up forthe side of bureaucracy have started to think of how strategy to be being done to increase servicewhich with quality. one of strategy guarantying public get service which in desiring him it is throughapplying of service charter or citizen charter.